2020
DOI: 10.5435/jaaos-d-20-00556
|View full text |Cite
|
Sign up to set email alerts
|

Shared Decision-making in Orthopaedic Surgery

Abstract: Shared decision-making (SDM) is the process by which the physician and the patient collaborate to arrive at the evidence-based treatment that best aligns with the patient's individual goals of care. The implementation of SDM practices is especially important when an invasive surgical procedure is among the treatment options. Ideally, the variation in the patient treatment choice would mirror the variability in patient goals rather than variation in a physician's ability to communicate effectively. Potentially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 40 publications
0
23
0
Order By: Relevance
“…In our clinical practice, we have found that shared decision-making and decision-aid tools assist in eliciting patients' preferences, goals, and functional status, which is then used to make a treatment decision that aligns with their preferences, goals, and functional demands. 6,7,19 Because strong evidence suggests that no difference in radiographic or patient-reported outcomes exist based on fixation technique for complete articular or unstable distal radius fractures (after 3 months), we advocate for the use of a fixation technique driven by the fracture pattern and patient characteristics. In the illustrated case, we felt a volar approach and volar locking plate would allow adequate visualization and capture and neutralize forces as a fixed-angle construct by transmitting forces from the distal fragments to the radial shaft.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our clinical practice, we have found that shared decision-making and decision-aid tools assist in eliciting patients' preferences, goals, and functional status, which is then used to make a treatment decision that aligns with their preferences, goals, and functional demands. 6,7,19 Because strong evidence suggests that no difference in radiographic or patient-reported outcomes exist based on fixation technique for complete articular or unstable distal radius fractures (after 3 months), we advocate for the use of a fixation technique driven by the fracture pattern and patient characteristics. In the illustrated case, we felt a volar approach and volar locking plate would allow adequate visualization and capture and neutralize forces as a fixed-angle construct by transmitting forces from the distal fragments to the radial shaft.…”
Section: Discussionmentioning
confidence: 99%
“…In our clinical practice, we have found that shared decision-making and decision-aid tools assist in eliciting patients' preferences, goals, and functional status, which is then used to make a treatment decision that aligns with their preferences, goals, and functional demands. 6,7,19…”
Section: Discussionmentioning
confidence: 99%
“…Physicians at our institution particularly utilize PROM data in clinical encounters to discuss progress following surgical procedures or nonoperative treatments. Therefore, any and all attempts at improving their integration may yield benefits for improved patient care 24 . There have been numerous studies that have demonstrated the utility of incorporating PROMs in this fashion [25][26][27] .…”
Section: Discussionmentioning
confidence: 99%
“…Another concept this study raises [5] is the use of a shared decision-making model for decisions regarding surgery in patients with articular fractures of the knee. In shared decision-making, a decision should be shared with patients rather than made for them [6]. It seems clear from this study that not all patients with tibial plateau fractures will benefit from surgical fixation.…”
Section: Where Do We Need To Go?mentioning
confidence: 99%